PENGARUH UKURAN PERUSAHAAN, ANAK PERUSAHAAN, LEVERAGE DAN PROFITABILITAS TERHADAP AUDIT DELAY STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR ANEKA INDUSTRI DAN INDUSTRI BARANG KONSUMSI - Ikhyanuddin Ikhyanuddin (Institut Agama Islam Negeri (IAIN) Bone, 2021)
ABSTRACTThis research was conducted to examine the effect of company size, subsidiaries, leverage and profitability on audit delay. Audit delay experienced by the company can harm various parties related to the company and cause a decline in the company's image in the eyes of investors. Audit delay is the time span for completion of the annual financial statement audit, measured based on the number of days it takes to obtain an independent auditor's report on the company's annual financial statement audit, from the date of the company's financial statement to the date stated in the independent auditor's report. The factors that are considered to influence audit delay are company size, subsidiaries, leverage and profitability. The sample selection used in this study is purposive sampling with the number of samples obtained as many as 59 manufacturing companies in various industrial sectors and consumer goods industries during the period 2017-2019. Data analysis using multiple linear regression analysis. The results showed that company size and leverage have a positive and significant effect on audit delay, while subsidiaries and leverage have a negative and insignificant effect on audit delay. Simultaneously, company size, industry type, audit committee, and KAP size.